2019
DOI: 10.35137/jabk.v6i3.329
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Struktur Modal, Profitabilitas, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Manufaktur Sektor Industri Makanan Dan Minuman Tahun 2013-2017

Abstract: This study aims to analyze the effect of Capital Structure, Profitability and Company Size on the Value of Manufacturing Companies in the Food and Beverage Industry Sector in Indonesia. This research was conducted on annual data of manufacturing companies in the food and beverage industry in the form of DER, ROA and Ln data for the period 2013 -2017. The results of this study indicate that partially the capital structure has a positive and significant effect on the value of manufacturing companies listed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Meanwhile, research (Priyatama and Pratini, 2021) has a significant positive effect. In this study, the measurement uses the natural logarithm (Ln) value of the total asset (Dewi and Damayanti, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, research (Priyatama and Pratini, 2021) has a significant positive effect. In this study, the measurement uses the natural logarithm (Ln) value of the total asset (Dewi and Damayanti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pecking order theory which governs the capital structure wants to use funds obtained from inside enterprises since it reduces risk. A study (Nurwulandari, 2021) found that capital structure has a negative effect but another study (Dewi & Damayanti, 2019) has a positive effect. To calculate it this study uses the Debt to Asset Ratio (DAR).…”
Section: Introductionmentioning
confidence: 99%